A Review of Postprint: Books and Becoming Computational - Szokolyai, Dóra (AMERICANA E-journal of American Studies in Hungary, 2022)
Postprint: Books and Becoming Computational N. Katherine Hayles New York: Columbia University Press, 2021 231 pages ISBN 978-0-23119-824-0